Personality Competence, Authority and Change Vision; Transformative Leadership in Building Madrasah Competitive Advantage - Sulhan, Moh; rifai, ilyas (JURNAL AL-TANZIM, 2023)
This study aims to explain the personality competencies of madrasah leaders, authority and the vision of change in leadership in bringing madrasahs towards competitive advantage. This research uses a qualitative approach. Data sources and data collection techniques were obtained from interviews, observations, and documentation. Data analysis was performed using a flow model: data collection, data reduction, presentation and conclusion. The findings of this study indicate that transformative leadership can bring madrasah to play a vital role as educational institutions with competitive Islamic characteristics that have advantages that align with the times' challenges. The transformative leadership of superior madrasah can be found in madrasah leaders who have visionary views, can position themselves as agents of change, can position themselves as the organisation's driving force, can deal with complexity, ambiguity and uncertainty, and have a social vision and thinking skills. Therefore madrasah need to adopt a transformative leadership model to move forward and be competitive in navigating change.